Characterization of the cytokine storm reflects hyperinflammatory endothelial dysfunction in COVID-19 - Sims, Jonathan T. (J Allergy Clin Immunol, 2021)
BACKGROUND: Physicians treating patients with coronavirus disease 2019 (COVID-19) increasingly believe that the hyperinflammatory acute stage of COVID-19 results in a cytokine storm. The circulating biomarkers seen across the spectrum of COVID-19 have not been characterized compared with healthy controls, but such analyses are likely to yield insights into the pursuit of interventions that adequately reduce the burden of these cytokine storms. OBJECTIVE: To identify and characterize the host inflammatory response to severe acute respiratory syndrome coronavirus 2 infection, we assessed levels of proteins related to immune responses and cardiovascular disease in patients stratified as mild, moderate, and severe versus matched healthy controls. METHODS: Blood samples from adult patients hospitalized with COVID-19 were analyzed using high-throughput and ultrasensitive proteomic platforms and compared with age- and sex-matched healthy controls to provide insights into differential regulation of 185 markers. RESULTS: Results indicate a dominant hyperinflammatory milieu in the circulation and vascular endothelial damage markers within patients with COVID-19, and strong biomarker association with patient response as measured by Ordinal Scale. As patients progress, we observe statistically significant dysregulation of IFN-γ, IL-1RA, IL-6, IL-10, IL-19, monocyte chemoattractant protein (MCP)-1, MCP-2, MCP-3, CXCL9, CXCL10, CXCL5, ENRAGE, and poly (ADP-ribose) polymerase 1. Furthermore, in a limited series of patients who were sampled frequently, confirming reliability and reproducibility of our assays, we demonstrate that intervention with baricitinib attenuates these circulating biomarkers associated with the cytokine storm. CONCLUSIONS: These wide-ranging circulating biomarkers show an association with increased disease severity and may help stratify patients and selection of therapeutic options. They also provide insights into mechanisms of severe acute respiratory syndrome coronavirus 2 pathogenesis and the host response.